Quantifying the inverse spin-Hall effect in highly doped PEDOT:PSS - Qaid, Mohammad M.; Mahani, M. R.; Sinova, Jairo; Schmidt, G. (Physical Review Research, 2020)
We present a systematic investigation of the inverse spin-Hall effect (ISHE) in the π-conjugated polymer poly(3,4-ethylenedioxythiophene):poly(4-styrenesulfonate) (PEDOT:PSS). Using a number of reference experiments, we are able to identify and isolate side effects which obscure the small but finite inverse spin-Hall effect in the polymer. We employ a sample geometry in which the contact areas and the area of spin current injection are laterally separated, which allows us to distinguish the ISHE from thermovoltages induced by nonreciprocal magnetostatic spin waves (MSSW) and from the ISHE induced by spin pumping through the polymer into the contacts. With an additional control experiment, we can even quantify the Nernst effect, which also needs to be taken into account. With these results, we can unambiguously show that the ISHE is present in this material, albeit at a level which requires a dedicated sample design and careful consideration of various artifacts.
CRIS-Team Scopus Importer:2023-03-27